ACADEMIC TEACHERS' PREFERENCES IN SELECTING SCIENTIFIC DATABASES - Kocira, Sławomir; Kuboń, Maciej; Malaga-Toboła, Urszula; Kwaśniewski, Dariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The objective of the paper was to determine the preferences of academic teachers in the selection of databases of scientific publications. Material consists of the results of research carried out with the diagnostic survey methods carried out with the questionnaire technique among the scientific employees and students of the selected Polish higher schools: University of Life Sciences in Lublin, University of Agriculture in Krakow. 135 scientific employees and 140 full-time students of the second cycle studies participated in the survey. University teachers the most often used publications in scientific journals and publications in the Internet. All students that took part in the questionnaire used scientific publications in the Internet and information included in the Internet. Databases of the Polish scientific publishing houses, Elsevier database, and Google Scholar database are the most useful in the scientific work. Students search for publications only in the Polish databases of publishing houses and Google Scholar base.